Ferroportin-inhibitor salt: patent evaluation WO2018192973. (3rd July 2021) - Kadam, Snehal; Khaitan, Megha; Banerjee, Paromita; Mandhare, Anita
ABSTRACT: Introduction: Iron is a crucial element necessary for blood formation in the body and its normal growth. However, irregular metabolism of iron due to absence of an elimination mechanism may deposit excess iron in the organs (iron overload) leading to metabolic disorders. Interactions between the iron regulatory peptide hormone, hepcidin and the iron exporter ferroportin plays major role in regulating the iron metabolism. Mutations in the ferroportin encoding genes, and dysregulation of hepsidin production often results in iron overload resulting in conditions like hemochromatosis, β-thalassemia, and sickle cell anemia. Until today, there is no efficacious treatment available for managing iron overload targeting ferroportin inhibition via oral administration. Areas Covered: Novel salts of substituted benzoimidazole compounds useful for the prophylaxis and/or treatment of iron overload are claimed. These compounds act as hepcidin mimetic and inhibit the ferroportin thereby preventing iron overload. The claimed actives are useful in the treatment of disease conditions such as neurodegenerative and cardiac diseases triggered by iron overload. Preclinical studies of these salts on mouse model are also discussed. Expert Opinion: Prevention and/or treatment of iron overload is critical. The claimed compounds are the first oral drug candidate to treat iron overload and reach the pre-clinical development stage.